Heritability of resistance to potato late blight in an F1 population of elite potato cultivars - Grisales Vásquez, Nancy Yohana; Cotes Torres, José Miguel (Revista Ceres, 2022)
Phytophthora infestans is the most important disease in potato crops. Its control is based on the use of chemical products that have developed pathogen resistance and high economic and environmental impacts. To reduce these effects, the use of plant varieties or cultivars resistant to this pathogen has been proposed. The aim of this study was to evaluate the heritability of resistance to this pathogen in a population of elite Solanum phureja genotypes. In this study, 1,355 clones with three replicates from 20 families were included in the evaluation. Heritability was assessed in the broad and narrow senses. Results of the relative area under the disease progress curve varied between 0.08 and 0.64, indicating that the population contains genes that code for resistance. Heritability in both directions (narrow 0.022 and broad 0.255) showed significant differences, indicating an influence of dominance genetic effects and environmental effects. Thus, to use these genotypes in potato breeding programs, hybridization methods should be used instead of selection methods.